2022
DOI: 10.3347/kjp.2022.60.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Peptide Antibody Specific to the Adenylyl Cyclase-Associated Protein of Acanthamoeba castellanii

Abstract: Acanthamoeba keratitis (AK) is a rare infectious disease and accurate diagnosis has remained arduous as clinical manifestations of AK were similar to keratitis of viral, bacterial, or fungal origins. In this study, we described the production of a polyclonal peptide antibody against the adenylyl cyclase-associated protein (ACAP) of A. castellanii, and evaluated its differential diagnostic potential. Enzyme-linked immunosorbent assay revealed high titers of A. castellanii-specific IgG and IgA antibodies being p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
3
4
0
Order By: Relevance
“…In the previous study, ACAP antibodies demonstrated A. castellanii-specificity to both trophozoite and cyst forms when these were co-cultured with HCE cells [24]. Here, we confirmed the specificity of ACAP antibodies to A. castellanii trophozoites and cysts cocultured with HCE cells, F. solani, S. aureus, and P. aeruginosa (Figure 1A), thus signifying their potential for differential AK diagnosis.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In the previous study, ACAP antibodies demonstrated A. castellanii-specificity to both trophozoite and cyst forms when these were co-cultured with HCE cells [24]. Here, we confirmed the specificity of ACAP antibodies to A. castellanii trophozoites and cysts cocultured with HCE cells, F. solani, S. aureus, and P. aeruginosa (Figure 1A), thus signifying their potential for differential AK diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it is difficult to accurately discern exactly how much Acanthamoeba antigen is contained within these samples. However, in our previous study, we reported that ACAP antibodies could detect the presence of Acanthamoeba from cell lysate at concentrations as low as 0.01 μg [24]. Combining these two results, our…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations